Rheumatoid Arthritis in Hail Region, Saudi Arabia - Mohammed Abdullah Alhadi, Sulaiman Zaid S Alamri, Ayman Mukhtar A Alzaid; Ahmed Abdulhamid Alanazi, Khalid Fahad Alanazi, Khalied Sulaiman Alanazi; Abdulaziz H Alazmi, Ahmad Jawad Alsmeel; Yasser Musallam Alrehaili, Mohammed Abdulrahman E Alali; Maha A. Alqadri, Alanoud M. Alhalwan (International Journal of Innovative Research in Medical Science, 2017)
Background: Rheumatoid Arthritis (RA) is a chronic inflammatory disease most commonly exists in developed countries. The distribution of RA is common among females and it differs greatly from nation to nation. The aim of the study: The aim of the current study is to determine the pattern of RA in both inpatient and outpatients who have been already diagnosed in the rheumatology unit at King Khalid Hospital (KKHH) during the years 2009-2012, Hail district, Kingdom of Saudi Arabia (KSA). Patients and Methods: The current study is a retrospective study involving the diagnosed patients whom attending (KKHH) for the rheumatology clinic during the period of 4 years (2009-2012) Patients’ data were gathered over the period of the study, according to the American College of Rheumatology (ACR) standards for RA. Results: Females were found to be commonly affected than males and their ages were mainly over 35 years with negative family history. The majority of patients experienced an insidious onset with intermittent course. The commonest extra-articular manifestation was ophthalmological manifestations, while the main associated diseases were hypertension, diabetes mellitus and hypothyroidism. The main systemic features were arthritis, morning stiffness as well as fatigue. The most sensitive test in the diagnosis of RA was the anti-cyclic citrulinated peptide antibodies (anti-CCP AB). Conclusion & recommendations: Demographic features were similar to those recorded by others. There is a must for more inclusive studies to detect the prevalence of RA in whole Hail region. A nationwide program for RA is needed to increase the awareness of Saudi population about the importance of early diagnosis of RA, which will help greatly the rheumatoid patients.